2015
DOI: 10.1093/nar/gkv1382
|View full text |Cite
|
Sign up to set email alerts
|

A novel RNA-binding mode of the YTH domain reveals the mechanism for recognition of determinant of selective removal by Mmi1

Abstract: The YTH domain-containing protein Mmi1, together with other factors, constitutes the machinery used to selectively remove meiosis-specific mRNA during the vegetative growth of fission yeast. Mmi1 directs meiotic mRNAs to the nuclear exosome for degradation by recognizing their DSR (determinant of selective removal) motif. Here, we present the crystal structure of the Mmi1 YTH domain in the apo state and in complex with a DSR motif, demonstrating that the Mmi1 YTH domain selectively recognizes the DSR motif. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 31 publications
4
78
0
Order By: Relevance
“…Recent studies have shown that many YTH domains are readers of the highly abundant N 6 -methyladenosine (m 6 A) RNA modification (Dominissini et al., 2012, Luo and Tong, 2014, Yue et al., 2015). However, Mmi1 recognizes a hexanucleotide UNAAAC motif within DSRs and is not specific for m 6 A (Harigaya et al., 2006, Kilchert et al., 2015, Wang et al., 2016, Yamashita et al., 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that many YTH domains are readers of the highly abundant N 6 -methyladenosine (m 6 A) RNA modification (Dominissini et al., 2012, Luo and Tong, 2014, Yue et al., 2015). However, Mmi1 recognizes a hexanucleotide UNAAAC motif within DSRs and is not specific for m 6 A (Harigaya et al., 2006, Kilchert et al., 2015, Wang et al., 2016, Yamashita et al., 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Our demonstration that mutation of five of these conserved amino acids had no effect on Mmi1-YTH binding to DSR RNA prompted us to conclude that Mmi1 YTH has a distinctive RNA binding site. While we were preparing this work for publication, Wang et al (2016) reported the crystal structure of Mmi1(322-488) in complex with a 10-mer RNA containing a consensus DSR hexamer (pdb 5EIM), which revealed that the DSR RNA binds on the face of the protein opposite the "aromatic cage" and is indeed a novel binding mode vis à vis the m 6 A reader clade of YTH proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structures of the METTL3-METTL14 complex demonstrated that METTL3 is the only protein to bind SAM and identified residues in the catalytic motif of METTL3 that are critical for methylation (Sledz & Jinek 2016, P. Wang et al 2016, X. Wang et al 2016).…”
Section: M6a Writersmentioning
confidence: 99%
“…Additionally, these researchers showed that purified METTL14 does not have methyltransferase activity, in contrast to the earlier finding that reported methyltransferase activity from purified METTL14. Although it is now clear that METTL14 does not transfer a methyl group to RNA, METTL14 plays a critical role by binding substrate RNA by forming interactions with METTL3 that enhance its enzymatic activity and by positioning the methyl group for transfer to adenosine (Sledz & Jinek 2016, P. Wang et al 2016, X.…”
Section: M6a Writersmentioning
confidence: 99%
See 1 more Smart Citation